Erosive and osteoarthritic structural progression in early rheumatoid arthritis - McWilliams, Daniel F.; Marshall, Michelle; Jayakumar, Keeranur; Doherty, Sally; Doherty, Michael; Zhang, Weiya; Kiely, Patrick D.W.; Young, Adam; Walsh, David A. (Oxford University Press, 2016)
OBJECTIVES: To investigate factors associated with joint damage in early RA, and how comorbid OA might influence patient assessment and outcomes. METHODS: Baseline radiographs of hands and feet from 512 participants in the Early RA Network cohort, and after 3 (+/-1) years, 166 of those participants yielded complete scores for RA [erosions, joint space narrowing (JSN)] and OA [JSN, osteophytes (OST)] using validated atlases. DAS28-P is the proportion of DAS28 attributed to patient-reported factors. Adjusted odds ratios were calculated using logistic regression. RESULTS: OA was common at baseline in early RA (40% hand and 48% foot) and associated with RA radiographic score. Higher baseline RA scores were associated with increasing age and ESR, and lower DAS28-P. OST scores were associated with higher age. DAS28 and patient-reported outcomes improved, whereas RA and OA radiographic scores deteriorated by follow-up. Erosive progression was predicted by higher baseline erosions, female gender, better mental health and lower DAS28-P. Hand OST progression was predicted by baseline OST scores. Inflammatory disease activity was associated with erosive, but not with OA progression. Baseline hand OA predicted worse physical function at follow-up, but radiographic progression did not explain changes in patient-reported outcomes. CONCLUSION: OA is a common comorbidity that might confound radiographic and clinical assessment, but does not fully explain erosive progression or patient-reported outcomes in early RA. Early RA management should address psychosocial factors and comorbidities, as well as joint inflammation.